Studi Kritis Bahan Ajar Mata Pelajaran Pendidikan Agama Islam Materi Ibadah Haji dan Kurban Kelas V SDN Bangbayang Cisolok Sukabumi - Cacang Cacang; Siti Qomariyah; Hasbullah Karim Al Fauzi; Ridwan Hermawan (Jurnal Budi Pekerti Agama Islam, 2025)
The low level of students’ understanding of Islamic practices and values in daily life remains a significant challenge in the teaching of Islamic Religious Education (IRE) at the elementary school level. The teaching of IRE on the topic “Hajj and Qurban” in Grade V at SDN Bangbayang, Cisolok District, plays a strategic role in shaping Islamic character and instilling noble moral values in students. This study aims to critically examine the learning objectives, teaching materials, instructional methods, evaluation system, references, and teaching resources used in the learning process. The research employed a qualitative approach with data collected through classroom observation, interviews with teachers and students, and an analysis of instructional documents. The findings reveal that, in general, the teaching of IRE in Grade V has been implemented in accordance with the objectives and curriculum standards. Teachers have designed teaching modules based on the basic competencies and learning goals outlined in the curriculum. However, several aspects still require further development. Among these are the limited relevance of the learning materials to students’ everyday experiences, the lack of integration of technology-based media, and an evaluation process that places greater emphasis on cognitive aspects while paying less attention to affective and psychomotor domains. This situation indicates that while the learning process is carried out in line with procedural standards, students’ comprehension of Islamic values in practical and contextual terms remains insufficient. Therefore, strengthening the understanding of Islamic teachings in real-life contexts is essential so that students not only acquire theoretical knowledge but are also able to internalize and practice Islamic values in their daily lives. The teaching module currently used is adequate, yet further development is needed to make learning more practical, contextual, and impactful in fostering a strong Islamic character among students.